Effects of Robusta coffee (Coffea canephora) brewing on levels of RANKL and TGF- β1 in orthodontic tooth movement - Herniyati Herniyati; Ida Bagus Narmada; Soetjipto Soetjipto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Orthodontic tooth movement will be followed by periodontal ligament and alveolar bone remodeling. Orthodontic mechanical force (OMF) will be distributed through the teeth to periodontal ligament and alveolar bone and then will generate local pressure resulting in bone resorption and tension areas that will form new bone. Robusta coffee contains caffeine, chlorogenic acid and caffeic acid. Caffeine may increase osteoclastogenesis, and caffeic acid has antioxidant effects that may reduce oxidative stress in osteoblasts. Purpose: This study conducted to analyze the effect Robusta coffee steeping on levels of RANKL and TGF-β1 in orthodontic tooth movement. Method: 16 male rats were divided into 2 groups. Group C: rats given OMF, Group T: given OMF and coffee brew at 20 mg/ 100 g BW. OMF in rats was conducted by applying ligature wire on the molar-1 (M-1) and both incisivus of right maxilla. Subsequently, M-1 of right maxilla was moved to mesial with a Niti closed coil spring. Observations were made on days 15 and 22 by taking the GCF by putting paper point on the gingival sulcus of mesio- and disto-palatal areas of M-1 of right maxilla to determine the levels of RANKL and TGF-β1 using ELISA method. Result: The administration of coffee brew was effective to increase levels of RANKL and TGF-β1 in the compression and tension areas (p <0.05). RANKL levels in compression area were higher than in the tension area (p <0.05), while the levels of TGF-β1 in the tension area were higher than in the compression area (p <0.05). Conclusion: The administration of coffee brew was effective to increase the levels of RANKL and TGF-β, therefore it might improve alveolar bone remodeling process.